2013
DOI: 10.1002/bip.22243
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the roles of sulfated glycosaminoglycans in islet amyloid polypeptide amyloidogenesis and cytotoxicity

Abstract: Glycosaminoglycans (GAGs) are found in association with virtually all extracellular protein deposits related to amyloid diseases. Particularly, GAGs were shown to enhance fibrillogenesis of the islet amyloid polypeptide (IAPP), a peptide hormone whose aggregation is associated with Type-II diabetes pathogenesis. However, the exact molecular mechanism by which GAGs enhance IAPP amyloidogenesis remains unclear as well as the implications of cell surface GAGs in IAPP-mediated cytotoxicity. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 45 publications
4
60
0
Order By: Relevance
“…The pro-amyloidogenic effect of heparin on IAPP fibril formation has been previously described (26,31). Here, we confirm this effect by thioflavin T assay and electron microscopy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The pro-amyloidogenic effect of heparin on IAPP fibril formation has been previously described (26,31). Here, we confirm this effect by thioflavin T assay and electron microscopy.…”
Section: Discussionsupporting
confidence: 90%
“…Prefibrillar species are thought to be the primary mediators of amyloid toxicity (10,34,35,42). Rapid amyloid formation in the presence of heparin may deplete these prefibrillar species, thus accounting for decreased toxicity in the presence of heparin after 6 h in our studies and an overall protective effect in another study (31). A similar effect was observed with amyloid-beta in the presence of methylene blue (43) and ellagic acid (44), compounds that promote fibrillization, protect against amyloid-associated toxicity, and inhibit oligomer accumulation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In a recent paper, Carufel et al (56) demonstrated that the removal of cell surface GAGs had no effect on IAPP-induced cytotoxicity, measured 24 h after exposure to Ն25 M hIAPP. This is not unexpected because formation of fibrillar species and, therefore, cytotoxicity should occur at such supraphysiological concentrations of hIAPP well before 24 h, independent of the presence or absence of GAGs.…”
Section: Discussionmentioning
confidence: 99%
“…On its own, this peptide demonstrates no ability to form fibrils, yet upon addition of heparin to the solution, a prompt increase in thioflavin T (ThT) fluo-D r a f t 14 rescence was observed (Madine et al 2013). Similar effects were observed with polypeptides that are known for their propensity to aggregate and whose depositions are associated with pathological states, such as IAPP, TTR, β2-microglobulin and apomyoglobin (De Carufel et al 2013;Noborn et al 2011;Relini et al 2008;Vilasi et al 2011). Whether this occurs because GAGs directly influence the conformational transition between the native and amyloidogenic states and/or because GAGs increase the local concentration of pre-fibrillar species remains to be confirmed.…”
Section: Mechanistic Contributions Of Gags In Amyloid Assemblymentioning
confidence: 92%